Childcare Educators' Understandings of Early Communication and Attachment. Issue 4 (December 2016) - Jovanovic, Jessie; Brebner, Chris; Lawless, Angela; Young, Jessica
GIVING VOICE TO THE discipline-specific knowledge and pedagogical practices of childcare educators, this paper attempts to explore new ways of defining educators' work with young children, given the post-structural turn in Australian and international early childhood policy. Three focus groups (n = 8 children's education and care services; n = 19 educators) were held in metropolitan Adelaide (South Australia) to explore their professional understandings of early communication and attachment development. Childcare educators described the relational and communicative elements of their work that supported or constrained their capacity to understand individual children's socio-emotional needs at enrolment, during transitions and in day-to-day routines. Whether attachment relationships were forged or being built, these educators explained how emotional reciprocity and an understanding of the child through secure attachment relationships enabled them to notice young children's communication abilities and needs, and vice versa. While the findings illuminate the expertise childcare educators bring to their work, we argue that there is a need to further explore how this expertise shapes their programs, practices and professional development needs.